No longer off the menu: the welcome re-emergence of food onto the nutrition agenda - Haddad, Lawrence J. (2003)
The proceedings include all main contributions (plenary lectures, special lectures, keynote lectures) presented at the 17th International Congress of Nutrition, held in Vienna, Austria, in August 2001. Following the outline of the congress program, this book covers nearly all aspects of modern nutrition, namely major and minor nutrients and their biological relevance, recommendations, guidelines and policy on nutrition, nutrition in health and disease, nutrition of specific population groups, advances and trends in nutrition research, advances in food production, food processing, food security and safety. One major topic of the congress was the focus on ‘Africa: nutritional problems of regions – the future of a continent’, all main lectures of this symposium are also included in the proceedings. The proceedings give a comprehensive review of the present knowledge and future perspectives of nutrition by the worldwide most prominent scientists in a resourceful form of one volume. Not only participants of the 17th International Congress of Nutrition will appreciate this publication, but also nutritional scientists, food scientists as well as public health officers dealing with health policy and food safety will find it a most useful update of their knowledge on the state of the art level of scientific expertise and for future perspectives in all sections of nutrition sciences.